Hubungan jumlah trombosit dengan fungsi trombosit pada pasien penyakit ginjal kronis tahap akhir pre-hemodialisis - Ahsan Tanio Daulay; Savita Handayani; Dairion Gatot (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction : Renal failure is condition where kidney cannot fitter blood waste and toxins adequately. One of complication is bleeding diathesis causes insufficiency of platelet function, coagulation cascade or fibrinolysis system activation. Method :Analytic observaiional research from September-Dece mber 2014 to 31 pre-dialyzed subject.Conclusion :Nocorrelation among high serum creatinine and urea with platelet count. bleeding lime,and platelet aggregation. Nocorrelation between platelet count and function (bleeding time and platelet aggregation).Result : Of 31 subject, mean of c;ge 50.71(S0=10.91) years old; Platelet 250,548 (SD=98,268)fmm3 with thrombocytopenia 19.4% case; bleeding time 4.77 (SD=3.03) minutes;with prolong bleeding time 19.4% case and 3.2% of it is thrombocytooe nia; hypoaggregation, 19.4%case. No significant correlation between platelet count and platelet function;among serum creatinine with platelet count and function;and urea with platelet count and functions. Key Words :chronicrenaldisease; platelet; platelet aggregation